The prevalence of insulin resistance in polycystic ovarian syndrome cases at a tertiary care hospital: a cross sectional study - Borse, Rama D.; Kurkal, Nidhi S.; Abhade, Aditi H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Insulin resistance (IR) is defined clinically as the inability of a known quantity of exogenous or endogenous insulin to increase glucose uptake and utilization in an individual as much as it does in a normal population PCOS is a disease of heterogeneous disturbance of reproductive, endocrine and metabolic functions. The objective of the study was to study the prevalence of insulin resistance in polycystic ovarian syndrome cases. Methods: The present cross sectional study was carried out at Obstetrics and Gynecology department, MGM medical college, Kalamboli, Navi Mumbai for a period of 2 years from 2011 to 2013 on total of 50 women aged between 16-39 years, coming to OPD with complaints of menstrual irregularities, infertility or hirsutism. After initial assessment, pelvic ultrasonography was done in these women to confirm the diagnosis of polycystic ovaries. Results: Majority 26 (52%) cases were in age group of 16-25 years and, majority 19 (38%) cases were in overweight (25-29.99) group. There were 21 (42%) women with insulin resistance When chi square test was applied to assess the association between BMI and insulin resistance, it was found to be statistically significant. (p=0.01). Conclusions: The prevalence of abnormal glucose tolerance, dyslipidemia, insulin resistance and metabolic syndrome was observed to be high in PCOS. We conclude that physician should consider that early recognition to reduce the incidence and severity of associated potential sequelae.